2021
DOI: 10.1002/ijc.33475
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide scan of long noncoding RNA single nucleotide polymorphisms and pancreatic cancer susceptibility

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is projected to become the second cancer‐related cause of death by 2030. Identifying novel risk factors, including genetic risk loci, could be instrumental in risk stratification and implementation of prevention strategies. Long noncoding RNAs (lncRNAs) are involved in regulation of key biological processes, and the possible role of their genetic variability has been unexplored so far. Combining genome wide association studies and functional data, we investigated the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Further, in most of the studies, the roles/mechanisms of the identified proteins in the pathogenesis of PDAC (e.g., why, and how the expression of proteins are correlated with the extent that they are secreted in normal or diseased conditions) remains unclear due to the singularity of techniques used thus limiting the interpretation of the significance of the study. This by no means only applies to proteomics but other fields of research as well (e.g., genomic [231,232], epigenomic-DNA methylation [233], single-cell transcriptomic [234] and metabolomics approaches [50,235]). One way to solve this is via the integration of multi-omics technologies that combine various approaches such as genomics, epigenomics, transcriptomics and metabolomics, together with proteomics.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Further, in most of the studies, the roles/mechanisms of the identified proteins in the pathogenesis of PDAC (e.g., why, and how the expression of proteins are correlated with the extent that they are secreted in normal or diseased conditions) remains unclear due to the singularity of techniques used thus limiting the interpretation of the significance of the study. This by no means only applies to proteomics but other fields of research as well (e.g., genomic [231,232], epigenomic-DNA methylation [233], single-cell transcriptomic [234] and metabolomics approaches [50,235]). One way to solve this is via the integration of multi-omics technologies that combine various approaches such as genomics, epigenomics, transcriptomics and metabolomics, together with proteomics.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Moreover, rare high-penetrance mutations and high-frequency lowpenetrance variants, discovered through genome-wide association studies (GWASs), contribute, alone or in combination, to the genetic susceptibility of PDAC (7)(8)(9)(10)(11)(12)(13)(14)(15). Additional susceptibility variants have been identified through large multicentric gene candidate approaches and through secondary analysis of published GWAS data (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The number of identified loci is, however, very small if compared with breast, prostate or colorectal cancers and the fraction of the heritability they explain is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our results expand the knowledge of the genetic PC risk through miRNA-related SNPs and show the usefulness of functional prioritization to identify genetic polymorphisms associated with PC risk. Feng et al, 2019;Gentiluomo et al, 2019a,b;Xu et al, 2019;Yang et al, 2019;Corradi et al, 2021). Only a small number of susceptibility loci for PC risk have been found thus far.…”
Section: Introductionmentioning
confidence: 99%